Deciphering Cadmium (Cd) Tolerance in Newly Isolated Bacterial Strain, Ochrobactrum intermedium BB12, and Its Role in Alleviation of Cd Stress in Spinach Plant (Spinacia oleracea L.) - Renu, S.; Sarim, Khan Mohd.; Singh, Dhananjaya Pratap; Sahu, Upasana; Bhoyar, Manish S.; Sahu, Asha; Kaur, Baljeet; Gupta, Amrita; Mandal, Asit; Thakur, Jyoti Kumar; Manna, Madhab C.; Saxena, Anil Kumar (Frontiers in Microbiology, 2022)
A cadmium (Cd)–tolerant bacterium Ochrobactrum intermedium BB12 was isolated from sewage waste collected from the municipal sewage dumping site of Bhopal, India. The bacterium showed multiple heavy metal tolerance ability and had the highest minimum inhibitory concentration of 150 mg L–1 of Cd. Growth kinetics, biosorption, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier transform infrared (FTIR) spectroscopy studies on BB12 in the presence of Cd suggested biosorption as primary mode of interaction. SEM and TEM studies revealed surface deposition of Cd. FTIR spectra indicated nitrogen atom in exopolysaccharides secreted by BB12 to be the main site for Cd attachment. The potential of BB12 to alleviate the impact of Cd toxicity in spinach plants (Spinacia oleracea L.) var. F1-MULAYAM grown in the soil containing Cd at 25, 50, and 75 mg kg–1 was evaluated. Without bacterial inoculation, plants showed delayed germination, decrease in the chlorophyll content, and stunted growth at 50 and 75 mg kg–1 Cd content. Bacterial inoculation, however, resulted in the early germination, increased chlorophyll, and increase in shoot (28.33%) and root fresh weight (72.60%) at 50 mg kg–1 of Cd concentration after 75 days of sowing. Due to bacterial inoculation, elevated proline accumulation and lowered down superoxide dismutase (SOD) enzyme activity was observed in the Cd-stressed plants. The isolate BB12 was capable of alleviating Cd from the soil by biosorption as evident from significant reduction in the uptake/translocation and bioaccumulation of Cd in bacteria itself and in the plant parts of treated spinach. Potential PGP prospects and heavy metal bioremediation capability of BB12 can make the environmental application of the organism a promising approach to reduce Cd toxicity in the crops grown in metal-contaminated soils.